Benzalkonium runoff from roofs treated with biocide products – In situ pilot-scale study. (15th September 2015) - Gromaire, M.C.; Van de Voorde, A.; Lorgeoux, C.; Chebbo, G.
Abstract: Roof maintenance practices often involve the application of biocide products to fight against moss, lichens and algae. The main component of these products is benzalkonium chloride, a mixture of alkyl benzyl dimethyl ammonium chlorides with mainly C12 and C14 alkyl chain lengths, which is toxic for the aquatic environment. This paper describes, on the basis of an in-situ pilot scale study, the evolution of roof runoff contamination over a one year period following the biocide treatment of roof frames. Results show a major contamination of roof runoff immediately after treatment (from 5 to 30 mg/L), followed by an exponential decrease. 175–375 mm of cumulated rainfall is needed before the runoff concentrations become less than EC50 values for fish (280 μg/l). The residual concentration in the runoff water remains above 4 μg/L even after 640 mm of rainfall. The level of benzalkonium ions leaching depends on the roofing material, with lower concentrations and total mass leached from ceramic tiles than from concrete tiles, and on the state of the tile (new or worn out). Mass balance calculations indicate that a large part of the mass of benzalkonium compounds applied to the tiles is lost, probably due to biodegradation processes. Graphical abstract: Highlights: Benzalkonium runoff induced by roof maintenance practices is investigated. Measurements were performed on 12 concrete and ceramic tile test beds over 13 month. Concentrations from 6 to 27 mg/l of benzalkonium are measured in the first 30 mm. Concentrations decrease rapidly over time following a first order decay law. Concentrations remain in the range of EC50 for invertebrates (6 μg/l) after 13 month.